1984
DOI: 10.1021/bi00321a043
|View full text |Cite
|
Sign up to set email alerts
|

Biogenesis, transit, and functional properties of the insulin proreceptor and modified insulin receptors in 3T3-L1 adipocytes

Abstract: The biogenesis, intracellular transport, and functional properties of the insulin proreceptor and modified insulin receptors were studied in hormone-responsive 3T3-L1 adipocytes. After control cells were labeled with [35S]Met for 7 min, the principal polypeptide that was precipitated by anti-insulin receptor antibodies had a molecular weight (Mr) of 180 000. This initial precursor was rapidly converted (t1/2 = 35 min) to a 200-kilodalton (kDa) polypeptide, designated the insulin proreceptor, by the apparent po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
1

Year Published

1985
1985
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 60 publications
0
4
1
Order By: Relevance
“…Hedo & J. M. Podskalny, unpublished work). Other laboratories have reported similar-sized precursors of the insulin receptor in 3T3-L1 adipocytes (Deutsch et al, 1983;Salzman et al, 1984;Ronnet et al, 1984) and IM-9 lymphocytes (Jacobs et al, 1983). However, the present report demonstrates the existence of the .…”
Section: Discussioncontrasting
confidence: 43%
“…Hedo & J. M. Podskalny, unpublished work). Other laboratories have reported similar-sized precursors of the insulin receptor in 3T3-L1 adipocytes (Deutsch et al, 1983;Salzman et al, 1984;Ronnet et al, 1984) and IM-9 lymphocytes (Jacobs et al, 1983). However, the present report demonstrates the existence of the .…”
Section: Discussioncontrasting
confidence: 43%
“…This suggests that it may be an incompletely processed proreceptor molecule that does not exhibit the proper conformation for ligand binding or AbP3 recognition. Certainly, incompletely or improperly processed mammalian insulin proreceptors have been reported not to bind insulin (23). The difference, however, is that in D. melanogaster the 170-kDa protein appears to be largely or completely incorporated into the receptor oligomer and to be disposed with the rest of the complex on the cell surface.…”
Section: Resultsmentioning
confidence: 99%
“…These intermediates are sensitive to endoglycosidase H and neuraminidase resistant. Salzman et al (44) and Herzberg et al (45) reported that the mature a-and /-subunits from 3T3-L1 adipocytes and IM-9 lymphocytes contain both endoglycosidase H-sensitive and -insensitive sugar side chains. The latter report also showed that endoglycosidase F could not remove all the sugar side chains from the /3-subunit but treatment with a chemical deglycosylating agent resulted in an additional decrease in molecular weight suggesting the presence of 0-linked side chains.…”
Section: Resultsmentioning
confidence: 99%